The Influence of Experiential Marketing and Integrated Marketing Communications on Visitor Loyalty - Butarbutar, Novita; Sherly, Sherly; Sinaga, Onita Sari; Doloksaribu, Winda Sri Astuti; Sudirman, Acai (IJBLE Scientific Publications Community Inc., 2023)
In responding to various tourism problems and competition between industries, as well as increasing the spirit of creativity in entrepreneurship in Indonesia, a special marketing strategy is needed in the tourism sector. In the context of tourism in the Lake Toba tourist area, several factors, such as experiential marketing and integrated marketing communication, can influence visitor loyalty. The main aim of this research is to analyze the influence of experiential marketing and integrated marketing communications on visitor loyalty in the Lake Toba tourist area. This research uses a literature and field research design with a causal associative approach with 130 respondents. The results of the data analysis confirm that there is a positive and significant influence between experiential marketing and integrated marketing communications on visitor loyalty. The conclusions of this research inform tourism actors in the Lake Toba area to utilize technology such as augmented reality (AR) or mobile applications to provide interactive experiences to visitors. Integrate technology to make it easier to access information and activities around Lake Toba. In addition, involving local communities in the planning and implementation of experiential marketing can create authentic tourist experiences. Through in-depth experiential marketing and good integration between various communication channels, Lake Toba can build a strong image and attract visitors to experience its beauty and uniqueness.